Evaluation of care for people living with Diabetes Mellitus according to the Care Model for Chronic Conditions (Research, Society and Development, 2021)
Objective: to evaluate the quality of care provided to people with Diabetes Mellitus followed up in public health services in a health region of Paraná after the implementation of the Care Model for Chronic Conditions. Method: cross-sectional study conducted with individuals living with Diabetes Mellitus in a small city in the state of Paraná. Data collection took place through secondary data, via electronic health record. Data analysis of categorical variables was expressed as percentages or absolute numbers. Kruskal-Wallis non-parametric test was used for analysis according to risk stratification. And to associate qualitative variables with risk stratification, the Chi-square and Fisher's exact test were used. Results: of the 361 individuals included in the study, 74.8% did not have a care plan record, 83.1% did not have access to an adequate number of consultations with health professionals, and most individuals did not undergo laboratory tests for metabolic control, 69% without LDL cholesterol test, 64.8% glycated hemoglobin test, 70.1% without renal staging. It was also evidenced that 93.6% of the individuals were not referred for evaluation by an ophthalmologist, and 57.6% did not reach the target of adequate body mass index. Conclusion: the care model for chronic conditions has not yet reached its peak of quality of care for people with Diabetes Mellitus in the city. The results point to the need for decision-making by local managers and longer observation of the intervention for evidence of impact on clinical outcomes.